GEOCHEMISTRY OF ALKALIC PALINGENESIS AND THE CARBONITE FORMATION ASSOCIATED WITH IT - Somoylov V.S.; Ronenson B.M.; Sobachenko V.N. (My University, 1987)
The authors studied the geochemistry of the geologically best surveyed northern part of the Il'men-Vishnevogorsk belt of alkalic rocks, i.e., the Vishnevogorsk complex, at three different erosion levels - near its roots (Potaniny Mountains), the intermediate (along the Kasli-Mauk railroad), and near the apex (north of the main intrusion). They determined the concentrations of potassium, sodium and a wide range of trace elements in 217 lump and 56 average samples. The results reveal marked differences in the composition of rocks formed at different levels of petrogenesis. The geochemical study has confirmed theories on the palingenic-plus-metasomatic origin of alkalic rocks of the Vishnevogorsk complex. The distinguishing feature of alkalic petrogenesis here is that it was controlled by the reaction of mantle-derived alkali-carbonate fluids with the crustal substrate.